Terbinafine versus itraconazole: a long-term, randomized, double-blind, clinical trial in chronic pulmonary aspergillosis. A pilote study - Gianfranco Schiraldi; Salvatore Lo Cicero; Claudio Rossetti; Delia Colombo; Michele Chiericozzi; Elvana Kola; Luigi Allegra (Journal of Health and Social Sciences)
Background: The frequency of pulmonary aspergillosis has been increasing for decades. Standard oral treatment is associated with tolerability problems and interactions with commonly used medications. Present data suggest that terbinafine may be a useful alternative for chronic forms. Methods: A randomised, double-blind, multicentre trial compared terbinafine (500 mg b.i.d) with itraconazole (200 mg b.i.d.) with respect to successful outcomes for up to 6 months in 24 patients with chronic pulmonary aspergillosis. The primary end-point was a global clinical assessment using a 4-point rating scale, including (thorax) X-ray or Tc features. Secondary end-points were mycological response, duration of treatment and tolerability based on adverse events, haematology, biochemistry and urinalyses. Results: The patients were randomly allocated to terbinafine or itraconazole. No patients discontinued terbinafine, while 2 of 12 patients discontinued itraconazole because of protocol violation (n=1) or withdrawal of consent (n=1). The mean ± SD duration of the treatment was longer in the terbinafine group (139.8 ± 43.6 days vs 120.5 ± 41.8 days). The clinical success rate was also higher with terbinafine (91.7% vs 70.0%), as was the eradication rate (100% vs 75%). The proportion of patients who reported adverse events was higher with itraconazole (7 of 12 vs 3 of 12). Conclusions: Terbinafine (500 mg b.i.d. for up to 6 months) is an effective, well-tolerated antifungal agent for the treatment of chronic infectious forms of pulmonary aspergillosis, representing a valid alternative to treatment with itraconazole in these clinical forms, due to better clinical efficacy and safety and lower costs vs new azoles.